Cucumber Varieties Are Affected by the Soil Pathogen Fusarium Spp. Tolerance - Marupov, A.; Sattarov, Q.; Tosheva, Yo. (American Journal of Botany and Bioengineering, 2025)
Navruz, followed by Zilol varieties, are the most resistant to fusarium wilt disease, and on the contrary, Ezgu, then Shirin hybrids are the most resistant to the disease.